Immobilization of Alcohol Dehydrogenase, Acetaldehyde Lyase, and NADH Oxidase for Cascade Enzymatic Conversion of Ethanol to Acetoin - Li, Xue-Yong; Huang, Jia-Ying; Zhou, Qiang; Xu, Yuan-Yuan; Prabhu, Ponnandy; Zhang, Ye-Wang (Energies (Basel), 2022)
Acetoin, a four-carbon hydroxyl-keto compound, is used in the food, pharmaceutical, and chemical industries. The cascade enzymatic production is considered a promising and efficient method to produce acetoin. However, the stability and compatibility of the enzymes under the same catalytic conditions are challenges that need to be resolved. In this work, alcohol dehydrogenase, acetaldehyde lyase, and NADH oxidase were selected to work at the same conditions to efficiently convert ethanol into acetoin. These three enzymes were immobilized on epoxy-modified magnetic nanomaterials to obtain highly stable biocatalysts. The stability and the immobilization conditions, including temperature, pH, enzyme–carrier ratio, and immobilization time, were optimized to obtain the immobilized enzymes with a high catalytic activity. The cascade reactions catalyzed by the immobilized enzymes yielded a high conversion of 90%, suggesting that the use of immobilized enzymes is a promising way to produce acetoin.